L17 Selective stimulation of shingosine-1-phosphate receptors (S1PRS) is beneficial in huntington's disease pre-clinical models. (13th September 2016) - Pardo, Alba Di; Amico, Enrico; Castaldo, Salvatore; Capocci, Luca; Maglione, Vittorio
Abstract : Background: Huntington's disease (HD) is a neurodegenerative disorder characterised by progressive worsening of behavioural, cognitive and motor function. Although rapid advancing basic and translational research has identified numerous potential targets for treating HD, no definitive cure is currently available. Promising research on alternative therapeutic approaches, however, offers new hope. Recent findings from us indicate that chronic administration of non selective agonist of sphingosine-1-phosphate receptors (S1PRs), FTY720, was neuroprotective and neurorestorative in R6/2 HD mouse model. Aims: The overall aim of this study was to investigate whether selective stimulation of specific S1PR subtypes might be beneficial in HD models. Methods: In vitro experiments were carried out in mouse striatal-derived cells expressing endogenous levels of wild type (STHdh7/7) or mutant (STHdh111/111) Htt respectively. Apoptosis and pro-survival pathways activation was assessed by Annexin V staining and Western Blotting respectively. In vivo experiments were performed in symptomatic R6/2 HD mice and age-matched wild type littermates. Animal motor performance was assessed by rotarod and horizontal ladder task. Results: Stimulation of S1PR1 and S1PR5 in vitro reduced apoptosis in HD striatal-derived cells and evocated the activation of pro-survival pathways. Importantly, administration of a S1PR5 selective agonist significantly ameliorated the overall motor function in R6/2 mice. Conclusions: Based on our findings we candidate specific S1PRs as novel molecular target for developing new potential therapies for the treatment of the disease.